Long non-coding RNA SeT and miR-155 regulate the Tnfα gene allelic expression profile. - Chrysoula Stathopoulou; Manouela Kapsetaki; Kalliopi Stratigi; Charalampos Spilianakis (PLoS ONE, 2017)
It is becoming increasingly appreciated that the non-coding genome may have a great impact on the regulation of chromatin structure and gene expression. The innate immune response can be mediated upon lipopolysaccharide stimulation of macrophages which leads to immediate transcriptional activation of early responsive genes including tumor necrosis factor alpha (Tnfα). The functional role of non-coding RNAs, such as lncRNAs and microRNAs, on the transcriptional activation of proinflammatory genes and the subsequent regulation of the innate immune response is still lacking mechanistic insights. In this study we wanted to unravel the functional role of the lncRNA SeT, which is encoded from the murine Tnfα gene locus, and miR-155 on the transcriptional regulation of the Tnfα gene. We utilized genetically modified mice harboring either a deletion of the SeT promoter elements or the mature miR-155 and studied the response of macrophages to lipopolysaccharide (LPS) stimulation. We found that decreased expression of the lncRNA SeT in murine primary macrophages resulted in increased mortality of mice challenged with LPS, which was corroborated by increased Tnfα steady state mRNA levels and a higher frequency of biallelically expressing macrophages. On the contrary, miR-155 deletion resulted in reduced Tnfα mRNA levels supported by a lower frequency of biallelically expressing macrophages upon stimulation with LPS. In both cases, in the absence of either lncRNA SeT or miR-155 we observed a deregulation of the Tnfα allele homologous pairing, previously shown to regulate the switch from mono- to bi-allelic gene expression. Although lncRNA SeT was not found to be a direct target of miR-155 its stability was increased upon miR-155 deletion. This study suggests a role of the non-coding genome in mediating Tnfα mRNA dosage control based on the regulation of homologous pairing of gene alleles and their subsequent biallelic expression.